2006
DOI: 10.1183/09031936.06.00101705
|View full text |Cite
|
Sign up to set email alerts
|

Time course of exhaled hydrogen peroxide and nitric oxide during chemotherapy

Abstract: This study was designed to assess the effect of differential leukocyte depletion during chemotherapy by monitoring the levels of exhaled hydrogen peroxide H 2 O 2 and nitric oxide (FeNO) present.In 39 patients with lung cancer (chronic obstructive pulmonary disorder up to stage II, median forced expiratory volume in one second 78% predicted), measurements were performed before a cycle of therapy (day 1), at least once during the cycle (day 8: n534; day 15: n519), and afterwards (days 21-29).There were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 33 publications
4
24
0
1
Order By: Relevance
“…Another study confirmed the observation of increased levels of FeNO and extended it demonstrating tumour-restricted tyrosine nitration in patients with cancer without increased NO synthase expression, suggesting an alteration of NO metabolism in the lungs of patients with cancer [46]. Other studies demonstrated a decrease in FeNO due to chemo-or radiotherapy in lung cancer [47,48]. Considering the wide range of FeNO in healthy subjects and the confounding effect of tobacco smoking on FeNO level, the described mediator increase is not likely to be able to discriminate patients with lung cancer from those without.…”
Section: Exhaled Monoxidessupporting
confidence: 61%
See 1 more Smart Citation
“…Another study confirmed the observation of increased levels of FeNO and extended it demonstrating tumour-restricted tyrosine nitration in patients with cancer without increased NO synthase expression, suggesting an alteration of NO metabolism in the lungs of patients with cancer [46]. Other studies demonstrated a decrease in FeNO due to chemo-or radiotherapy in lung cancer [47,48]. Considering the wide range of FeNO in healthy subjects and the confounding effect of tobacco smoking on FeNO level, the described mediator increase is not likely to be able to discriminate patients with lung cancer from those without.…”
Section: Exhaled Monoxidessupporting
confidence: 61%
“…The conclusion of the study was that oxidative stress occurs during lung resection, as higher H 2 O 2 concentration was found after lobectomy compared to baseline. In another study, the effect of chemotherapy was assessed on exhaled H 2 O 2 concentration in lung cancer patients, showing a significant decrease in this biomarker level by treatment [48]. No difference was found in the concentration of EBC 8-isoprostane between patients with lung cancer and control subjects [95].…”
Section: Other Markersmentioning
confidence: 99%
“…Hyperactivity of airways induced with ROS elicits the histamine release from mast cells and mucous secretion from epithelial cells (Lee et al, 2011). During acute asthma exacerbation these changes are associated with cell shedding, enhanced release of arachidonic acid and chemo-attractants (Calabrese et al, 2000) and increased release of hydrogen peroxide and nitrous oxide during exhale (Wewel et al, 2006;Nagaraja et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…NO ist schneller und leichter messbar, bei Vorschulkindern häufig die einzige Möglichkeit, die Atemwegsentzündung zu erfassen. [46], die durch neutrophile Granulozyten im Rahmen der unspezifischen Entzündung erzeugt werden [47].…”
Section: Raucherunclassified